MODEL PEMBINAAN BOLA VOLI TERPADU: EVALUASI MENYELURUH DARI ASPEK TEKNIK, TAKTIK - Daramendra; Habibi; Ignasius Kristiando; Khairul Anwar; Mario Carolus; Risky Nasution; Risky Ramadani; Dewi Endriani (STKIP Subang, 2026)
Developing excellence in volleyball requires a systematic and integrated approach. This study aims to formulate and evaluate an Integrated Volleyball Development Model that emphasizes the integration of basic technical skills and game tactics. The research method used is qualitative descriptive with an evaluative study approach applied to a youth volleyball club. Data were collected through field observations, in-depth interviews with the head coach, and motor skill tests of the athletes. The evaluation results indicate that the integrated development model, which combines physical technique training with real-time tactical simulations, improves attack accuracy efficiency by 25% and defensive effectiveness by 30%. The conclusion of this study confirms that the rigid separation of technical and tactical training has a negative impact on athletes’ decision-making on the court. The integrated model is recommended as a new standard in youth volleyball training curricula.